PENGUATAN KARAKTER KEBANGSAAN MELALUI PENDIDIKAN KEWARGANEGARAAN (PKN) PADA SISWA KELAS V SEKOLAH DASAR - Dyah Arti Mumpuni; Ahmad Muhibbin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to examine the strengthening of national character through learning Civic Education (PKn) in grade V elementary school. The research type is qualitative research with a case study approach. The research subjects were 36 fifth grade students at SDN 02 Pereng. Data collection techniques include documentation, observation, and interviews. Data analysis of the Miles and Huberman model, namely: data collection, reduction, presentation and conclusion drawing. Data validity was guaranteed through triangulation of sources and techniques. The results showed that the strengthening of national character through Civics learning can be carried out effectively and students are actively involved through innovative learning methods, such as discovery learning, lectures, and group discussions. In addition, school policies through out-of-class activities such as: flag ceremonies, commemoration of national holidays, social activities, and others also strengthen the internalization of national values, such as nationalism and Pancasila. Overall, this study confirms the importance of a holistic approach that integrates classroom learning and out-of-class activities in shaping students' national character, as well as making a significant contribution in building a young generation with integrity and love for the country.